Ketidakjujuran Akademik Pada Siswa SMP: Self Confidence dan Locus of Controls - Mardiyah, Jauharatul; Suryani, Suryani (Fakultas Psikologi Universitas Wisnuwardhana Malang, 2024)
Abstrak.Penelitian ini bertujuan untuk melihat pengaruh self confidence, locus of control terhadap academic dishonesty pada siswa SMP. Alat ukur yang digunakan dalam penelitian ini adalah self confidence scale (SCS), Internlity, Powerful Other and Chance Scale (IPC) dan academic dishonesty scale (ADS). Teknik pengambilan sampel menggunakan teknik probability sampling. Jumlah sampel 344 siswa SMP di Sumenep Metode analisis data yang digunakan untuk pengujian hipotesis adalah analisis linear berganda Hasil penelitian diperolehnilai Sig. 0,000 < 0,05. Hal tersebut menunjukkan self confidence dan locus of control berpengaruh terhadap terjadinya academic dishonesty. Abstract. This study aims to see the effect of self-confidence, locus of control on academic dishonesty in junior high school students. The measuring instruments used in this study are self-confidence scale (SCS), Internlity, Powerful Other and Chance Scale (IPC) and academic dishonesty scale (ADS). The sampling technique uses probability sampling technique. The number of samples is 344 junior high school students in Sumenep. The data analysis method used for hypothesis testing is multiple linear analysis. The results of the study obtained a Sig. value of 0.000 <0.05. This shows that self-confidence and locus of control have an effect on the occurrence of academic dishonesty.